ANALISIS IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DI RSUD dr. M. THOMSEN NIAS KABUPATEN NIAS TAHUN 2023 - Harefa, Beriman Putra (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
Hospital is a workplace that has a high risk for the safety and health of hospital human resources, patients, patient companions, visitors, and the hospital environment. Realizing an effective, efficient, integrated and sustainable implementation of Hospital Occupational Health and Safety (HOHS) requires the implementation of an Occupational Health and Safety Management System (OHSMS) in the hospital. This research aims to analyze the implementation of OHSMS in RSUD dr. M. Thomsen Nias. This research uses mixed methods with the explanatory sequential design that combines quantitative and qualitative research methods in sequence. The informants in this study amounted to 5 people. Quantitative data was collected by survey using a checklist form from annex 2 of Government Regulation No. 50 of 2012 as evidenced by document review and on-site observation. Qualitative data was collected by interview using guidelines from the quantitative data results. Based on the results of the study, the level of achievement of OHSMS implementation was obtained with an initial category audit of 56.25%, which is included in the category of less implementation. Of the 64 total criteria, there are 36 criteria that are appropriate and 28 criteria that are inappropriate. Commitment in the form of a written policy has not been made, but a decree has been issued to establish an OSH organization and committee. OHS planning has been made in the form of a work program. The implementation of the OHS plan has not been fully implemented by the OHS committee, but the hospital's efforts in implementing OHS are carried out by several related units such as the Infection Prevention and Control (IPC) Committee, the Hospital Facilities Maintenance Installation (HFMI) and the Environmental Installation. The implementation of OHSMS at RSUD dr. M. Thomsen Nias starting from the policy setting stage to evaluation has not been fully implemented properly according to Government Regulation No. 50 of 2012.